Evaluation of in-situ calibration of Chemcatcher passive samplers for 322 micropollutants in agricultural and urban affected rivers. (15th March 2015) - Moschet, Christoph; Vermeirssen, Etiënne L.M.; Singer, Heinz; Stamm, Christian; Hollender, Juliane
Abstract: In a large field study, the in-situ calibration of the Chemcatcher ® passive sampler – styrenedivinylbenzene (SDB) covered by a polyether sulfone (PES) membrane – was evaluated for 322 polar organic micropollutants. Five rivers with different agricultural and urban influences were monitored from March to July 2012 with two methods i) two-week time-proportional composite water samples and ii) two-week passive sampler deployment. All substances – from different substance classes with logKow −3 to 5, and neutral, anionic, cationic, and zwitterionic species – were analyzed by liquid-chromatography high-resolution tandem mass spectrometry. This study showed that SDB passive samplers are well-suited for the qualitative screening of polar micropollutants because the number of detected substances was similar (204 for SDB samples vs. 207 for composite water samples), limits of quantification were comparable (median: 1.3 ng/L vs. 1.6 ng/L), and the handling in the field and laboratory is fast and easy. The determination of in-situ calibrated sampling rates (field Rs ) was possible for 88 compounds where the R 2 from the regression (water concentration vs. sampled mass on SDB disk) was >0.75. Substances with moderately fluctuating river concentrations such as pharmaceuticals showed much better correlations than substances with highly fluctuating concentrations such as pesticides (R 2  > 0.75 for 93% and 60% of the investigated substances, respectively). Flow velocity (0.05–0.8 m/s) and temperature (5–20 °C) did not have an evident effect on the field Rs . It was observed that ionic species had significantly lower field Rs than neutral species. Due to the complexity of the different transport processes, a correlation between determined field Rs and logDow could only predict Rs with large uncertainties. We conclude that only substances with relatively constant river concentrations can be quantified accurately in the field by passive sampling if substance-specific Rs are determined. For that purpose, the proposed in-situ calibration is a very robust method and the substance specific Rs can be used in future monitoring studies in rivers with similar environmental conditions (i.e., flow velocity, temperature, pH). Graphical abstract: Highlights: SDB passive sampler perfectly suitable for qualitative screening of micropollutants. Broad substance spectrum detected, detection limits comparable with water samples. Robust field sampling rates were determined for 88 substances by in-situ calibration. Substances with highly fluctuating water concentrations are more difficult to quantify. Effects of flow velocity and temperature on field sampling rates were not evident.